2014
DOI: 10.7205/milmed-d-13-00090
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Biomechanical Changes Associated With Symmetrical Torso Loading During Simulated Marching

Abstract: The dose-response relationship between biomechanical variables and the magnitude of external loads is unclear. The use of different load distributions (e.g., pack types) may confound results because of changes in torso center of mass. Therefore, we examined the relationship between load magnitude and sagittal plane lower extremity mechanics of Soldiers walking with two symmetrically distributed loads. Fourteen Soldiers marched on a force-sensing treadmill at 1.34 m/s for 10 minutes with no load (BW_00) and whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…15,22 Our findings of reduced KEM in the ACLR limb are consistent with compensatory gait patterns present after ACL rupture, 4,6,13,20 ACLR, 3-5 physical therapy, 19 and several years after ACLR. 19 Reduced KEM in the ACLR limb is found across multiple functional tasks such as step ups, running, and drop jump landing, implicating the robustness of this biomechanical profile in the ACLR limb.…”
Section: Discussionsupporting
confidence: 82%
“…15,22 Our findings of reduced KEM in the ACLR limb are consistent with compensatory gait patterns present after ACL rupture, 4,6,13,20 ACLR, 3-5 physical therapy, 19 and several years after ACLR. 19 Reduced KEM in the ACLR limb is found across multiple functional tasks such as step ups, running, and drop jump landing, implicating the robustness of this biomechanical profile in the ACLR limb.…”
Section: Discussionsupporting
confidence: 82%
“…The quadriceps muscles act eccentrically during early stance to control knee flexion, whilst the plantar flexors act concentrically towards the end of stance to contribute to push-off Seay et al 2014). The increased gastrocnemius lateralis muscle activity suggests a greater plantar flexor force production was required for push-off when carrying a load of 35.5 kg, consistent with earlier findings which reported an increase in gastrocnemius activity with loads up to 33 kg .…”
Section: Effects Of Load Carriagesupporting
confidence: 88%
“…While load reportedly failed to produce any kinematic adaptations at the hip or knee, the addition of 20 and 40 kg body borne loads resulted in an increase of external flexion moments at both joints while running 18 . These extended limb postures when paired with high magnitude moments may prevent limb collapse, but further increase strain on the musculoskeletal system by aiding the transfer of high ground reaction forces up the kinetic chain of the body 25 . Further, high magnitude moments are indicative of an increase in mechanical work of the musculoskeletal system that occurs in an effort to prevent limb collapse.…”
Section: Military Load Carriagementioning
confidence: 99%
“…During a single-leg cut with body borne load, Brown et al 14 reported that military personnel exhibited a significant increase in peak hip and knee flexion, and hip adduction joint moments to successfully complete the maneuver. These elevated joint moments require greater force generation by the hip and knee musculature to prevent collapse of the limb, but increase the stresses placed on the musculoskeletal system and risk of injury 25,26,27 . Yet, to date, it is unknown if military personnel exhibit similar adaptations in lower limb biomechanics, and subsequent increased risk of musculoskeletal injury, when performing a single-leg cut with the small incremental changes of body borne load commonly worn during military related tasks (i.e.…”
Section: Sex Dimorphism In Load Carriage Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation